2017
DOI: 10.1186/s12951-017-0269-2
|View full text |Cite
|
Sign up to set email alerts
|

A retro-inverso cell-penetrating peptide for siRNA delivery

Abstract: BackgroundSmall interfering RNAs (siRNAs) are powerful tools to control gene expression. However, due to their poor cellular permeability and stability, their therapeutic development requires a specific delivery system. Among them, cell-penetrating peptides (CPP) have been shown to transfer efficiently siRNA inside the cells. Recently we developed amphipathic peptides able to self-assemble with siRNAs as peptide-based nanoparticles and to transfect them into cells. However, despite the great potential of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
54
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 67 publications
(86 reference statements)
8
54
1
Order By: Relevance
“…Studies have shown that D-amino acids based on a retro-inverso design are resistant to endogenous proteolysis and have long-lasting effects [31][32]. The retro-inverso FSH β 33-53 peptides exhibited similar advantages in our previous study [28].…”
Section: Preparation and Characterization Of Nanoparticle Complexessupporting
confidence: 64%
“…Studies have shown that D-amino acids based on a retro-inverso design are resistant to endogenous proteolysis and have long-lasting effects [31][32]. The retro-inverso FSH β 33-53 peptides exhibited similar advantages in our previous study [28].…”
Section: Preparation and Characterization Of Nanoparticle Complexessupporting
confidence: 64%
“…But CPP made up of natural L amino acids are susceptible to proteolysis. The retroinverso version CADY-K peptide has been tried which has been successful in protecting it from proteolysis as well as retaining the capacity for cell penetration and self-assembly in form of nanoparticle with siRNA (Obasse, Taylor, Fullwood, & Allsop, 2017;Vaissière et al, 2017). The retroinverso analog of 18 residue long peptide PYC98 not only has fivefold more inhibition of the activity of JNK1 toward c-Jun but it also inhibits JNK1 activity toward EGFR-derived peptide (Ngoei, Catimel, Milech, Watt, & Bogoyevitch, 2013).…”
Section: Attempts Of Mimetics Using Retroinverso and Modified Analogsmentioning
confidence: 99%
“…Among the diverse class of peptides, cell-penetrating peptides (CPPs) have been extensively utilized for delivery of therapeutics [13]. Different CPPs including TP10, MPG, CADY, PepFect 6 (PF6), PF14, TAT, R9, R9-hLF, RV peptides, LAH4, RICK were reported for siRNA delivery [14][15][16][17][18][19][20][21][22][23][24]. Among CPPs, RICK was reported to form self-assembled structure.…”
Section: Introductionmentioning
confidence: 99%